Modified Maxillary Palatal Ramp Prosthesis to Guide Mandibular Deviation Following Segmental Mandibulectomy for Squamous Cell Carcinoma - Rathee, Manu; Chahal, Sujata; Alam, Maqbul; Jain, Prachi (Journal of Dentistry Indonesia, 2022)
Benign or malignant tumor is one of the frequent causes of resection of the mandible. The extent and location of the tumor decides the mode of treatment of the neoplastic lesion. Surgical removal of oral neoplasm leads to an extensive resection of the mandible along with the associated structures. Objective: This case report describes the use of palatal ramp prosthesis to guide the mandible during movements and restore a stable occlusal relationship with an additional acrylic buccal pad to achieve partial esthetics. Case Report: A 30-years-old female patient reported with the inability to chew food following the mandibular resection of the left side. History of the patient revealed left side segmental mandibulectomy following surgery for squamous cell carcinoma of mandible. This case report describes the use of palatal ramp prosthesis to guide the mandibular deviation. Conclusion: The clinician must keep in mind the prosthetic intervention until and unless the reconstruction of the defect is planned. The rehabilitation of the defect should be done as soon as possible to prevent the mandibular deviation.